The effects of working capital management on SMEs profitability in Malaysia - Rahima, Abbas Ali (2015)
This study investigates the effect of working capital management on SMEs profitability in Malaysia using a sample of 66 SME manufacturing firms covering from 2006 until 2012. Ordinary least square (OLS) regression is used to estimate the relationship between the independent and dependent variables. The results show that, there is negative relationship between working capital management measures i.e. days account receivables (DAR), inventory turnover in days (ITID), and cash conversion cycle (CCC) and SMEs profitability proxies i.e. return on assets (ROA) and return on equity (ROE) except for net operating profit (NOP) which is having positive effect with CCC. Furthermore, the study shows that there is positive relationship between days account payables (DAP) and SMEs profitability measured by (ROA and ROE) but having a negative relation with NOP. The results imply that Profitability of SME manufacturing firms depends upon effective working capital management. Therefore, this study suggests that SME manufacturing companies can improve their profitability by managing working capital properly.